The rights of nature a legal revolution that could save the world - Boyd, David R., (David Richard) 1964- (ECW Press, 2017)
"Palila v Hawaii. New Zealand's Te Urewera Act. Sierra Club v Disney. These legal phrases hardly sound like the makings of a revolution, but beyond the headlines portending environmental catastrophes, a movement of immense import has been building...in courtrooms, legislatures, and communities across the globe. Cultures and laws are transforming to provide a powerful new approach to protecting the planet and the species with whom we share it. Lawyers from California to New York are fighting to gain legal rights for chimpanzees and killer whales, and lawmakers are ending the era of keeping these intelligent animals in captivity. In Hawaii and India, judges have recognized that endangered species...from birds to lions...have the legal right to exist. Around the world, more and more laws are being passed recognizing that ecosystems...rivers, forests, mountains, and more...have legally enforceable rights. And if nature has rights, then humans have responsibilities. In The Rights of Nature, noted environmental lawyer David Boyd tells this remarkable story, which is, at its heart, one of humans as a species finally growing up. Read this book and your world view will be altered forever."...
Includes bibliographical references and index
Keywords: Environmental law; Animal rights